2000
DOI: 10.1080/00420980020080371
|View full text |Cite
|
Sign up to set email alerts
|

Singapore : The Development of an Intelligent Island and Social Dividends of Information Technology

Abstract: The paper traces the development of Singapore as an 'intelligent' island through an identi cation of the various social policy arrangements which have harnessed new information technology modes in their delivery. At home, at work, on the road, in public service and in the court room, the emergence of new IT arrangements is a matter of fact in Singaporean lives. Attention is drawn to the 'unencumbered' character of IT policy-making in Singapore, a characteristic which is the outcome of little or no strong polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Singapore is another key reference: since the early 1990s its government adopted a branding policy presenting Singapore as an ambitious 'intelligent city', creating conditions for the development of clusters of globally competitive tech industries in different domains, from information technology to the biomedical sector (Arun and Yap, 2000). In these and other Asian experiences, a central role has been played by the 'developmental state'.…”
Section: The Cognitive-communicative Capital Of Citiesmentioning
confidence: 99%
“…Singapore is another key reference: since the early 1990s its government adopted a branding policy presenting Singapore as an ambitious 'intelligent city', creating conditions for the development of clusters of globally competitive tech industries in different domains, from information technology to the biomedical sector (Arun and Yap, 2000). In these and other Asian experiences, a central role has been played by the 'developmental state'.…”
Section: The Cognitive-communicative Capital Of Citiesmentioning
confidence: 99%
“…Singapore has probably been the city that identified most with the imaginary of the intelligent city. In fact, it funded a huge computing infrastructure project destined to both businesses and citizens as part of its branding as an 'intelligent island' (Arun and Yap 2000;Olds and Yeung 2004). However, many more cities around the world have integrated the vision of the ICT city into their development strategies.…”
Section: The Smart City In Urban Development Policiesmentioning
confidence: 99%
“…IT has now infiltrated almost all aspects of Singapore life: schools, home, work, transport and public service. 16 A 2005 Infocomm Development Agency of Singapore (IDA) survey revealed that 74 per cent of Singapore households owned a desktop or laptop computer, and 66 per cent of these homes had Internet connectivity. 17 In its Global Information Technology Report 2003Report -2004, the World Economic Forum ranked Singapore as one of the most network-ready nations in the world.…”
Section: Singapore As Case Studymentioning
confidence: 99%